Internationalization of vocational and higher education systems: A comparative-institutional approach - Justin J. W. Powell; Heike Solga (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2008)
This paper sketches a comparative-institutional approach that seeks to enhance our understanding of internationalization and the resultant national dynamics of institutional change in vocational and higher education systems. Focusing on change at the nexus of general and vocational skill formation institutions, we discuss shifts in the relationship between higher education and vocational training systems. How are such national systems responding to the exogenous pressures of international diffusion and Europe-wide Bologna and Copenhagen processes more specifically? Changes in the competition between the differentially institutionalized organizational fields of general and vocational education also imply the adjustment of individual pathways, participation rates, and life chances. Three complementary studies serve to compare and contrast the transformation of Germany's vocational and higher education systems. The comparison of Germany, Great Britain and the United States analyzes the diffusion and cross-national transfer of educational models in specific historical periods. To highlight different national responses to internationalization and Europeanization, Germany will also be compared with Switzerland and Austria as well as with France. If the first study charts primarily the origins of models to be emulated because of their global salience (cultural-cognitive dimension), then the second and third comparative studies analyze the normative and regulative dimensions, showing the consequences of institutional change processes for the on-going competition between these organizational fields. – – Dieses Papier versucht darzulegen, welche Forschungsleitfragen, theoretischen Zugänge und welches Forschungsdesign für eine Untersuchung von Internationalisierung und nationalen Veränderungsdynamiken von Berufsbildungs- und Hochschulsystemen in Ansatz zu bringen sind. Gegenstand des vergleichenden Forschungsprojekts ist die Untersuchung des institutionellen Wandels an den Schnittstellen von höherer Allgemein- und beruflicher Bildung - mit der Perspektive auf Veränderungen im beruflichen Bildungssystem. Welche Veränderungen ergeben sich im Berufsbildungssystem und seinem Verhältnis zum System der höheren Allgemeinbildung durch den exogenen isomorphen Veränderungsdruck, etwa durch Bologna und Kopenhagen? Mit detaillierten Analysen der nationalen Bildungsstrukturen und -pfade werden gegenwärtige Veränderungsprozesse und -dynamiken untersucht. Von zentraler Bedeutung sind dabei Aspekte des Wettbewerbs zwischen den beiden unterschiedlich institutionalisierten und organisierten Bildungsbereichen. Ferner werden die Implikationen des festgestellten institutionellen Wandels für die Beteiligung der Individuen an höherer Allgemein- und beruflicher Bildung eruiert. Die Ländervergleiche dienen als Kontrastfolien für den Wandel des deutschen Berufsbildungssystem: Deutschland wird in den drei vergleichenden Projekten mit den USA und Großbritannien, der Schweiz und Österreich sowie Frankreich verglichen. Ziel dieser Ländervergleiche ist es, Institutionalisierungs- und Europäisierungsprozesse der kulturell-kognitiven, normativen, und regulativen Dimensionen zu analysieren und damit den Wettbewerb dieser organisatorischen Felder aufzuzeigen.
Keywords: 300; Berufsbildung; Hochschule; Bildung; Institutioneller Wandel; Kognition; Vergleich